Transient liquid phase Ag-based solder technology for high-temperature packaging applications - Sharif, Ahmed (2014)
A lead-free Ag-based soldering technique through transient-liquid-phase (TLP) bonding is proposed in this study for high-temperature microelectronic packaging applications. The solder paste, which contained Ag and Sn powders with a no-clean flux, was used to join Cu substrates. The setup was bonded at 250 °C for 10 minutes. The study focuses on mechanical and microstructural characterizations of the joints. The shear strength measured at 250 °C shows good high temperature performance of the joint. The effects of Ag and Sn contents on mechanical, electrical and thermal properties of sintered bulk Ag–Sn samples were also investigated independently. The results demonstrate that the Ag–Sn TLP bonding is an effective interconnection method for harsh environment electronic packaging.